ASPEK TEKNIS OPERASIONAL YANG MEMPENGARUHI TIMBULAN SAMPAH DI KECAMATAN KOTA SIGLI KABUPATEN PIDIE DAN SOLUSI PENANGANANNYA - Yusbindar Yusbindar; Eldina Fatimah; Suhendrayatna Suhendrayatna (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2020)
The current technical operational waste management in Sigli City District, starts from preparing individual and communal containers. The collection process is carried out directly and indirectly. Garbage that has been collected is transferred to a Temporary Waste Disposal Site (TPS). The processing process through composting, incineration, and recycling is only done by a small part of the population, while waste processing at large-scale TPS is not yet available, such as making compost and so on. Waste that has no economic value is transported to the Final Disposal Site (TPA). The processing aspect in the operational technical cycle is not maximally carried out. If all technical aspects of solid waste management operations can be carried out properly by the District Government of Sigli City, the generation of residential waste can be minimized. The residual waste generation in Sigli City reaches 13,887 m3 / day. This study aims to analyze the effect of technical operational aspects on waste generation in settlements, and identify solutions for handling waste generation. This research uses quantitative methods through questionnaires and qualitative methods through observation and interviews. Respondents were aimed at residents of the City of Sigli as many as 100 people. The results showed that the operational technical aspects that had a significant effect on waste generation were the aspects of container, collection, removal, transportation, and final disposal aspects. The solution for handling waste generation in the container aspect needs to procure individual waste containers and communal trash containers, on the collection aspect it is necessary to implement collection through street sweeping patterns in public areas, as well as socializing to the community to be able to participate in sorting waste that has economic value, in this aspect. for relocation, it is necessary to provide a location and TPS facility in a village that does not yet have a TPS, in the transportation aspect it is necessary to conduct socialization to waste collectors from city cleanliness institutions, to meet the requirements for transportation equipment, and in the aspect of final disposal it is necessary to carry out gas processing, and provide a location that is far from settlements for landfill development.